Pengaruh Variasi Jenis Sampah dan Jumlah Larva BSF (Black Soldier Fly) pada Penguraian Sampah Organik Rumah Tangga - Firstyaline, Jennycha Ananda Budhi; Oktaviananda, Cyrilla; Sriyana, Herman Yoseph; Rahayu, Lucia Hermawati (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2025)
The increase in population and household consumption can lead to an increase in the volume of household waste. The increase in the volume of household waste will become a serious problem if no processing efforts are made. If household-scale waste processing is not carried out, it can result in the accumulation of the volume of organic waste in the Integrated Waste Management Site (TPST). One of the efforts that can be made to process waste at the household scale is by decomposing it using BSF larvae (maggot). Household waste generally consists of vegetable scraps and fruit peels. Vegetable and fruit waste is classified as organic waste which contains many nutrients that are utilized by BSF larvae as a food source in their breeding. The ability of BSF larvae to eat organic waste makes them widely used as one of the biodecomposter agents. This study aims to determine the effect of waste type and variation in the number of maggot on feed conversion efficiency, waste reduction index and characteristics of maggot produced. This study was conducted with a complete randomized design method with two independent variables and two repetitions. The physical characteristics of maggot which include, digested feed conversion efficiency (ECD), waste reduction index (WRI), and protein content in dried maggot. The type of garbage has no significant effect on the value of feed conversion efficiency (ECD), has a significant effect on the value of the waste reduction index (WRI) and has a very significant effect on protein content. The variation in the number of maggot has a very significant effect on the value of feed conversion efficiency (ECD) and waste reduction index (WRI) and has a significant effect on protein content.